Cs2CO3-promoted [3 + 2] cycloaddition providing an easy protocol toward imidazo[1, 2-a]indole derivatives1. Issue 92 (8th October 2015) - Zhang, Li-Dan; Qiu, Jiang-Kai; Kong, Li-Fang; Hao, Wen-Juan; Miao, Jiao-Na; Wu, Shuo; Jiang, Bo; Tu, Shu-Jiang
<x xml:space="preserve">Abstract</x> A base-promoted [3 + 2] cycloaddition for the construction of multi-functionalized imidazo[1, 2-a]indole derivatives with good yields has been accomplished.